Methachronical cutaneous metastasis of squamous carcinoma of the anal canal - Saeta Campo, Rebeca; Apio Cepeda, Ana; Velayos García, Paula (Cirugía del Uruguay, 2022)
The right therapy of anal cancer needs a multidisciplinary management of surgeons, pathologists, radiotherapists and radiologist. The treatment of squamous cell carcinoma of the anal canal is well-known when the patient presents a locally disease, nevertheless, there is a lack of information with the advanced anal cancer. We report a case of a 74-year-old woman with a solitary methachronical cutaneous metastasis of anal cancer which responded perfectly to surgery and radiotherapy.